(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The study analysed the moisture, ash, fibre, fat, protein, and carbohydrate content of different samples labelled A to E. The results showed that as the proportion of Cashew fruits increased in the jam, the moisture content also increased. The ash content remained consistent across all samples, indicating a stable mineral composition. The fibre content increased with a higher proportion of cashew fruits, indicating that cashew fruits contributed more fibre to the composite jam compared to pineapple. The fat and protein content were low and consistent across all samples, with pineapple being the primary contributor. The carbohydrate content varied based on the proportion of cashew fruits, with a higher carbohydrate content observed in samples with more pineapple. Overall, the composite jam can be considered a low-fat product, and its fibre and carbohydrate content depend on the proportion of cashew fruits. The study provided valuable insights for health-conscious consumers and highlighted the potential health benefits of incorporating more cashew fruits into the composite jam. The study’s results were compared with other studies, showing significant variations in moisture, ash, protein, and carbohydrate content, highlighting the importance of considering different fruit combinations and compositions in jam production. Sensory evaluations were conducted to assess the overall acceptability of the pineapple and cashew fruit jam. The results revealed that the blend with a higher percentage of cashew fruits (sample E) was more preferred by evaluators in terms of flavour, colour, taste, and texture. This underscores the importance of sensory attributes in influencing consumer preferences and satisfaction with food products. Overall, this study provides comprehensive insights into the proximate composition and sensory attributes of pineapple-cashew fruit jam, making it a valuable resource for food product development, consumer acceptance, and nutritional awareness. The findings can guide manufacturers in optimising the formulation of composite jams to meet consumer expectations and preferences, ultimately contributing to increased consumer satisfaction and positive brand perception in the market.